total immediate collective imminent terrestrial salvation (2019) by Tim Crouch - Aloysia Rousseau (Miranda: Revue Pluridisciplinaire du Monde Anglophone, 2020)
Theatre review of total immediate collective imminent terrestrial salvation by Tim Crouch, directed by Andy Smith and Karl James. Royal Court Theatre, London, 3-21 September 2019 (First performed at the Edinburgh International Festival from 7 to 25 August 2019).